Prestasi reservoir - Ismail, Abdul Razak; Hamid, Mohd. Fauzi; Abdul Manan, Muhammad (Penerbit UTM, 1998)
This book was translated from English to Malay. The early section of Chapter 1 (Reservoir performance) explains the influence of permeability on reservoir performance. Other topics covered in this book are vertical lift performance, choke performance, principles of gas lift, etc.